The Relationship between Hybrid Work Systems, Employee Well-Being, and Organizational Performance in the Service Sector in Indonesia - Anita Kusuma Dewi; Maulidia Berlianti; Hardini Ariningrum; Hasiatul Aini (Institut Bisnis dan Informatika Kesatuan, 2025)
The adoption of hybrid work systems, combining remote and in-office work, has transformed organizational management in Indonesia’s service sector. While these systems offer flexibility and efficiency, their impact on employee well-being and organizational performance in developing countries remains underexplored. This study investigates how hybrid work systems affect employee well-being and their collective influence on organizational performance in service companies, with a focus on the mediating role of well-being. A quantitative approach was employed, collecting data through structured surveys from 80 employees in banking, insurance, and consulting sectors across Jakarta, Surabaya, and Bandung. Data analysis used Structural Equation Modeling based on Partial Least Squares, suitable for small to medium sample sizes. The findings reveal that hybrid work systems significantly enhance employee well-being by improving work-life balance, autonomy, and reducing commuting stress. Well-being partially mediates the positive effect of hybrid work on organizational performance, particularly in service quality, productivity, and employee retention. This research highlights the strategic importance of hybrid work in achieving sustainable performance in Indonesia’s service sector, emphasizing the need for policies that balance flexibility with robust social and technological support to optimize employee well-being and organizational outcomes.